RELATIONSHIP BETWEEN LEARNING INTEREST WITH STUDENT RESULTS ON STANDARD COMPETENCY OVERHAUL COOLING SYSTEM IN CLASS XI TSM SMK KARSA MULYA PALANGKA RAYA 2016/2017 - Dede Juli Setiawan; Debora (Jurusan Pendidikan Teknologi Dan Kejuruan, 2018)
It has been found that there is less optimal learning outcomes of students for the course subject of standard overhaul cooling system indicated by the number of students having the low score at under KKM 70. Teachers have not known what the exact cause of this case. The relation of learning interest with learning outcome would be the research topic conducted to determine whether there is a significant positive relationship or even opposite between them thus it will be reference for teacher to improve student’s learning outcomes to be more optimal. This research used the survey method with correlation approach that is to know the relation of learning interest and student learning outcomes. The subject of this research is all students of class XI-TSM Karsa Mulya Palangka Raya involving 2 classes. The sample used is a saturated sample that takes both classes. The instrument used in this study is a questionnaire using Likert scale followed by the number of statements using 25 items that have been validated with 0.89 (reliability). The results obtained that the average score of student interest in the class XI-TSM is equal to 101.387 with as many as 48.39% or as many as 30 students have scores below average and 51.61% or as many as 32 students (scores above average). The student learning outcomes obtained an average score of 76.37 with 37.1% and 23 students have scores below the average learning achievement and as much as 62.9% or as many as 39 students have scores above the average. Moreover, the total students are 50 students expressing the successful target and 12 students were failed. The normality test results have obtained the student's interest in learning data is normally distributed. From the calculation obtained r xy (rcount) is 0.689, while the value of rtable with the significant level of 0.05 and degrees of freedom (db) n - 2 is 0.254. Thus, since (rhitung = 0.689)> (rtabel = 0.254) there is a significant correlation or correlation between learning Interest (X) with Learning Outcomes (Y). Then hypothesis testing is H0 rejected and Ha accepted (Ha: r ? 0). Furthermore, hypothesis testing using t-test has obtained tcount value> ttable (7,750> 2,000). Because thitung = bigger than ttabel then H0 rejected Ha accepted. All in all, the conclusion that there is a significant positive relationship between the learning interest with student learning outcomes on the course subject of standard overhaul cooling system in the class XI-TSM Karsa Mulya Palangka Raya at academic year 2016/2017.